2016
DOI: 10.1371/journal.pone.0158107
|View full text |Cite
|
Sign up to set email alerts
|

Initial Accuracy of HIV Rapid Test Kits Stored in Suboptimal Conditions and Validity of Delayed Reading of Oral Fluid Tests

Abstract: ObjectivesTo evaluate the effect of storing commonly used rapid diagnostic tests above manufacturer-recommended temperature (at 37°C), and the accuracy of delayed reading of oral fluid kits with relevance to HIV self-testing programmes.DesignA quality assurance study of OraQuick (OraSure), Determine HIV 1/2™ (Alere) and Uni-Gold™ (Recombigen®).MethodsConsecutive adults (≥18y) attending Ndirande Health Centre in urban Blantyre, Malawi in January to April 2012 underwent HIV testing with two of each of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…A previous study conducted in Malawi examined the pre‐use stability of OraQuick ® HIV test kits . 371 optimally stored and 375 pre‐incubated used devices were re‐read over a 12‐month period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study conducted in Malawi examined the pre‐use stability of OraQuick ® HIV test kits . 371 optimally stored and 375 pre‐incubated used devices were re‐read over a 12‐month period.…”
Section: Resultsmentioning
confidence: 99%
“…Methods that detect incorrect results and misinterpretation are required for individual care as well as for quality assurance. One approach, which has been utilized in early HIVST implementation studies, is for self‐testers to return used devices for delayed re‐reading by trained staff in parallel with self‐reported interpretation of results . However, delays between device use and re‐reading, and environmental storage conditions during this period could impair the validity of this method.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, seven participants did not use HIVST. The median age of the remaining 143 participants was 25 years (interquartile range [IQR], [22][23][24][25][26][27][28] with a median number of eight sexual partners in the prior year (IQR 4-19) ( Table 1). Most (58%) had received primary education, while 18% had no formal education.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…However, few studies have evaluated uptake of HIVST among MSM in sub-Saharan Africa [22,24] Novel, effective strategies are urgently needed to increase coverage of HIV testing services among MSM, and promote linkage to prevention, care and treatment services. Peer distribution of HIVST kits in MSM networks may increase access to HIV testing in Uganda where 33% of MSM had never tested for HIV in 2012 [8,9,12,25]. In a recent pilot intervention at the AIDS Support Organization (TASO) secondary distribution of referral coupons by MSM peers increased uptake of facility-based HIV testing [26].…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the OraQuick HIV‐1/2 antibody test kits for result stability post‐testing. They showed that while strongly reactive HIVST remained stable, 29% of initially non‐reactive kits converting to be weakly reactive false positive when read at least four days later, countering previous work which indicated OraQuick test kits were stable for up to a year . Re‐reading may be problematic and result in artificially inflated positivity rates; this finding led the WHO to recommend against any delayed readings of kits .…”
mentioning
confidence: 93%